2018
DOI: 10.1038/s41598-018-36046-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Peptide Composition and Bioactivity of Different Collagen Hydrolysate Batches on Human Osteoarthritic Synoviocytes

Abstract: Collagen hydrolysates (CHs) are heterogeneous mixtures of collagen peptides that are often used as nutraceuticals for osteoarthritis (OA). In this study, we compared the peptide composition and pharmacological effects of three different CH preparations (CH-Alpha®, Peptan® B 2000 and Mobiforte®) as well as their production batches. Our biochemical analysis using MALDI-TOF mass spectrometry and the ICPL™-isotope labelling method revealed marked differences between different CH preparations and even between some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Hence, the heterogeneous peptide composition and disparate possible pharmacological effects between various collagen hydrolysate sources suggest that the effect of a specific preparation cannot always be extrapolated to other formulations. This observation has been verified using different technologies in other studies comparing different source collagen hydrolysates that have similarly demonstrated different CH preparations can differ significantly in their peptide composition [76][77][78].…”
Section: Discussionsupporting
confidence: 61%
“…Hence, the heterogeneous peptide composition and disparate possible pharmacological effects between various collagen hydrolysate sources suggest that the effect of a specific preparation cannot always be extrapolated to other formulations. This observation has been verified using different technologies in other studies comparing different source collagen hydrolysates that have similarly demonstrated different CH preparations can differ significantly in their peptide composition [76][77][78].…”
Section: Discussionsupporting
confidence: 61%
“…Another issue that needs to be clarified is the role of the source of collagen and manufacturing processes on its therapeutic effects. In fact, it has been reported that different CH may have different peptide composition [43,44,88] and exhibit different effects on articular cartilage [43,44]. It may therefore be important to differentiate collagen derivatives according to source of collagen and manufacturing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no effective treatment for OA, only the therapy that slows or prevents OA progression [ 6 , 8 ]. So far most of the treatment methods (prescribing analgesics or nonsteroidal anti-inflammatory drugs (NSAIDs)) have focused on relieving pain and improving joint function without the possibility of solving the problem of the OA progression and complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%